Physico-Chemical Aquatic Sediment Study and Its Effect on Cl-, CO32- / HCO3- and SO42- Availability at Brantas Water Basin Source Brantas - Winioliski L.O Rohi Bire; Barlah Rumhayati; Atikah Atikah (Natural B, Journal of Health and Environmental Sciences, 2015)
The research about study of physico-chemical properties of aquatic sediment has been conducted for determining the availability of Cl-, CO32-/HCO3- and SO42- in Sumber Brantas stream. Sediment samples were collected from Sumber Brantas stream, Village of Sumber Brantas, Batu City in July-September 2014 on five different locations. Determination of pH using a pH meter, the determination of the composition of the sediment with the pipette method, determination of Cl- by argentometry, SO42- by turbidimetry and CO32-/ HCO3- by acid-base titration. The result showed that Sumber Brantas stream sediment relatively acidic and dominated by sand fraction. Anion distribution in Sumber Brantas stream sediment was HCO3- > SO42- > Cl- > CO32-. The distribution was influenced by Ksp value of the anion.